Trans-oceanic erotics: sexing indentureship. Issue 2 (22nd December 2022) - Wahab, Amar
Abstract : Through creative speculation and intervention, this research project probes the 'coolie homoerotic' (Wahab 2019) as a critical reflection on the place of the homoerotic and queerness within the trans-oceanic lifeworld of coolie indentureship. The four artworks presented are informed by a series of questions that might help to build a platform for queering indentureship and trans-oceanic space beyond identity recovery and respectability politics. In this regard, the work in progress is aimed at sexing indenture by (1) focusing on Brown same-sex sexual intimacies and erotic relations on coolie ships, as a way of undoing the historically constructed disconnect between the categories 'sex' and 'indentured labour', and (2) critically engaging the colonial heteropatriarchal discourse of 'sex/gender/sexuality' that continues to condition the unthinkability of same-sex relations in the context of indentureship and its legacies.